2011
DOI: 10.1007/s00383-010-2830-z
|View full text |Cite
|
Sign up to set email alerts
|

Usage of 64-detector-row spiral computed tomography volumetry in preoperative volume prediction in living donor liver transplantation in children

Abstract: Liver volume calculated by 64-detector-row spiral CT preoperatively can predict the actual graft weight, which is very useful in donor selection in LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Sakei et al [48] proposed another formula to calculate the standard liver volume of children undergoing liver transplantation (standard liver volume = 689.9 × body surface area -24.7), using CT images as a reference. Li et al [49] proposed the use of an equation (intraoperative weight = 0.844 × preoperative CT volume + 5.271) that can be useful to predict the actual graft weight (r = 0.885). Ribero et al [50] reported that the use of an estimated TLV, measured on the basis of correlation existing with body surface area (-794.41 + 1267.28 × body surface area), can identify about 11% of patients in whom liver volumetry directly calculated by CT images underestimates the risk of hepatic insufficiency.…”
Section: Imaging: Which Modality Should Be Chosen?mentioning
confidence: 99%
“…Sakei et al [48] proposed another formula to calculate the standard liver volume of children undergoing liver transplantation (standard liver volume = 689.9 × body surface area -24.7), using CT images as a reference. Li et al [49] proposed the use of an equation (intraoperative weight = 0.844 × preoperative CT volume + 5.271) that can be useful to predict the actual graft weight (r = 0.885). Ribero et al [50] reported that the use of an estimated TLV, measured on the basis of correlation existing with body surface area (-794.41 + 1267.28 × body surface area), can identify about 11% of patients in whom liver volumetry directly calculated by CT images underestimates the risk of hepatic insufficiency.…”
Section: Imaging: Which Modality Should Be Chosen?mentioning
confidence: 99%
“…For patients with end-stage liver disease, liver transplantation is the most effective treatment [2] . The great increase in the number of patients awaiting liver transplantation during the past years has led to a significant shortage of cadaveric organs [3] . Living-related liver transplantation has emerged as a valuable alternative, and allows healthy adults to donate a part of their own liver to a compatible recipient [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The preoperative liver volume measurements based on 3D anatomy imaging have been shown to agree with the actual volume of the liver resected at operation (17)(18)(19). The median volume difference between the portalvein-based and hepatic-vein-based anatomies in S6 was 73 mL.…”
Section: Discussionmentioning
confidence: 72%